(untitled) (Heritage, 2025)
: The paper explores the sociopolitical position of the “Serbian Resistance Movement” (1981-1989) as a liminal body between a social movement and an NGO. The paper first analyzes whether social movements in the SFRY could have been an alternative to NGOs that were politically active in “Western countries” and how this movement became a politically active body. Then, the question arises whether the “Serbian Resistance Movement” will anticipate the emergence of NGOs in Serbia that, after the collapse of the SFRY, deal with the position of Serbs in Kosovo and Metohija and the region and strive to solve problems that are officially within the jurisdiction of the state. The analysis shows that the “Serbian Resistance Movement” adopted the characteristics of an NGO, but used the strategies of social movements because the term “non-governmental organization” was not used in socialism and the leaders of the movement did not have a legitimate basis for political engagement parallel to the state as a non-party body.